On the measurement of changes in product quality in marginal intra-industry trade - Abdul Karim, Mohd Azhar; Elliott, Robert J. R. (Springer, 2008)
There is a long established thread of the international trade literature concerned with the measurement of intra-industry trade (IIT). Two distinct strands of the literature have developed: First, measures of marginal IIT that are concerned with the adjustment implications of volume-based changes in IIT; second, measures of vertical and horizontal IIT that are concerned with quality-based differences in IIT. This paper marries the two literatures to provide a new perspective on the smooth adjustment hypothesis debate and suggests the use of the marginal product quality index, a new measure of changes in quality in matched trade changes that complements dynamic measures of volume-based IIT.